Islam : a mosaic, not a monolith - Gregorian, Vartan (Brookings Institution Press, 2003)
For readers unfamiliar with the world's fastest-growing religion, Gregorian provides an accessible overview of its tenets, institutions, evolution, and historical role, along with insights into the current state of Muslim societies and the challenges they face.
Keywords: Islamic countries -- Politics and government -- 20th century.; Islam and politics -- Islamic countries.; Islamic renewal -- Islamic countries.; Nationalism -- Islamic countries -- History -- 20th century.; Islam and politics.; Islam et politique -- Pays musulmans.; Islamisme.; Renouveau islamique -- Pays musulmans.; Nationalisme -- Pays musulmans -- Histoire -- 20e siècle.; Pays musulmans -- Politique et gouvernement -- 20e siècle.; POLITICAL SCIENCE -- Political Process -- General.; RELIGION -- Islam -- General.; Islam and politics; Islamic renewal; Nationalism; Politics and government; Islamic countries; Islam; Islam.; Stromingen (cultuur); 1900-1999; History